Análise filogenética dos poliquetas portadores de tori: a linhagem dos Enterocoela - Assis, José Eriberto de (2013)
The first classifications for the annelids were presented within a peculiar group of worms grouped within Class Vermes. The group was initially divided into Errant Annelides, Tubicolous or Sedentary Annelides, Terricolous Annelids, and Freshwater Annelids. These classifications did not reflect common ancestry. With the advent of phylogenetic systematics, many proposals were made for other organisms, attempting to reflect true relationships. The first proposals for annelids and polychaetes appeared in the 90s, based on morphology, and attempted to confirm the monophyly of these two groups. In these analyses, the Pogonophora were reduced to a family of Polychaeta, the Siboglinidae. These results remained incongruent when compared to results obtained later from molecular data. Another phylogenetic proposal presented the Pogonophora as being close to the sedentary polychaetes, closely related to Owenia. In this proposal, the clade Metameria was established to group the annelids, Enterocoela and Deuterostomia. Pogonophora as a family of Polychaeta disregards the evolutionary relationships that this taxon shares with the deuterostomes. In the present work, polychaetes with tori were selected as the ingroups of the analysis, together with Pogonophora, and including Phoronida and Pterobranchia, in order to establish genealogical relationships among these taxa. For parsimony analyses molecular data from 18S rRNA, morphological data coded as binary (a/p), multistate, and combined data (multistate molecular and morphological data) were used. Several slightly different topologies appeared in our results on morphology and molecules. On the other hand, the combined data was similar to the topology obtained from multistate morphology. From these analyses, we hypothesize that sedentary polychaetes with tori (including Pogonophora) are strictly related to Phoronida and Deuterostomia, their tagmatization being considered a particularly important synapomorphy. Finally, we emphasize the paraphyletic nature of Protostomia, Spiralia, Trochozoa and Lophotrochozoa, which are contrasted to the monophyletic Metameria.